Variation in morphological attributes and yield of tomato cultivars (Research in Agriculture Livestock and Fisheries, 2016)
A pot experiment was carried out in the grill house of the Department of Seed Science and Technology, Bangladesh Agricultural University (BAU), Mymensingh during the period of mid December 2014 to mid April 2015. The experiment conducted with five treatments (five tomato genotypes) and employed in Completely Randomized Design (CRD) with four replications. Of the five genotypes two were obtained Japan (Pasta and Mimi) and the rest three from Bangladesh Agricultural Research Institute (BARI). Genetic variations appeared for morphological and phenological characters and yield attributes in the five tomato genotypes. Taller plants with higher number of branches were observed in the Japanese genotype (Mimi) while number of days required to initiate flower and fruit initiation and fruit maturity were shorter in BARI tomato 12 and BARI tomato 14. Flower and fruit productions plant-1 was higher in BARI released tomato cultivars, therefore, the tomato yield was also higher in those cultivars.Res. Agric., Livest. Fish.3(2): 287-294, August 2016